Initial Reports of the Deep Sea Drilling Project 1983
DOI: 10.2973/dsdp.proc.71.138.1983
|View full text |Cite
|
Sign up to set email alerts
|

Content, Type, and Thermal Evolution of Organic Matter in Sediments from the Eastern Falkland Plateau, Deep Sea Drilling Project, Leg 71

Abstract: The quantity, type, and maturity of the organic matter in Recent through Upper Jurassic sediments from the Falkland Plateau, DSDP Site 511, have been determined. Sediments were investigated for their hydrocarbon potential by organic carbon and Rock-Eval pyrolysis. Kerogen concentrates were prepared and analyzed in reflected and transmitted light to determine vitrinite reflectance and maceral content. Total extractable organic compounds were analyzed for their elemental composition, and the fraction of the nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In the geochemical study of Site 511, DSDP Leg 71, it was shown (Schaefer et al, 1983) that intervals bearing Type-Ill kerogens contained 20-45% benzene (as a fraction of total C 6 hydrocarbons). On the other hand, in the black shales of" Site 511, which have a Type-II kerogen, the benzene proportion ranged from 4 to 8% at a maturity range of 0.4 to 0.5% vitrinite reflectance (von der Dick et al, 1983). This source-controlled effect is also seen in Figure 4.…”
Section: Hole 530amentioning
confidence: 81%
“…In the geochemical study of Site 511, DSDP Leg 71, it was shown (Schaefer et al, 1983) that intervals bearing Type-Ill kerogens contained 20-45% benzene (as a fraction of total C 6 hydrocarbons). On the other hand, in the black shales of" Site 511, which have a Type-II kerogen, the benzene proportion ranged from 4 to 8% at a maturity range of 0.4 to 0.5% vitrinite reflectance (von der Dick et al, 1983). This source-controlled effect is also seen in Figure 4.…”
Section: Hole 530amentioning
confidence: 81%
“…Index map (inset) is modified from Sclater et al (1977). 5 to 7%, with values as high as 24%, in the lower Albian at Site 364 in the eastern Angola Basin. Average organic-carbon concentrations of 4 to 5% are typical of the Hauterivian-lower Aptian strata at Site 511 in the Argentine Basin (von der Dick et al, 1983), and less than 1% in the Aptian-Albian. The black-shale beds of Albian to Coniacian-Santonian age at Site 530 contain as much as 16.59b organic carbon with an overall average of 5.4% organic carbon as compared with less than 0.5% organic carbon in intercalated beds of red and green claystone (Meyers, Brassell, Hue, this volume).…”
Section: Organic-carbon-rich Strata In the Cretaceous Atlantic Oceanmentioning
confidence: 93%
“…However, at Site 511 sapropel deposition occurred during the early A!bian, whereas dysoxic clays were deposited from mid to late Albian time. This sequence represents the gradual ventilation of the basinalprovince of the Falkland Plateau (Deroo et al 1983;Von der Dick et al 1983).…”
Section: Late Aptianmentioning
confidence: 99%